1997
DOI: 10.1016/s0009-9236(97)90123-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of temazepam in primary insomnia: Assessment of the value of quantitative electroencephalography and saccadic eye movements in predicting improvement of sleep

Abstract: In subjects with primary insomnia the administration of 20 mg oral temazepam results in changes in both the pharmacodynamic measures and in quality of sleep. No individual correlations between the pharmacodynamic measures and quality of sleep were observed. We concluded that the investigated pharmacodynamic measures are of value in the first assessment of clinical efficacy and for the selection of the dose(s) to be investigated in subsequent trials that aim at showing clinical efficacy. However, the conclusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Tuk 116 found no significant reduction in PSG NOA at 20 mg. One study 117 reported data for subjective NOA at 20 mg (−0.2 awakenings compared to placebo).…”
Section: Number Of Awakeningsmentioning
confidence: 83%
See 2 more Smart Citations
“…Tuk 116 found no significant reduction in PSG NOA at 20 mg. One study 117 reported data for subjective NOA at 20 mg (−0.2 awakenings compared to placebo).…”
Section: Number Of Awakeningsmentioning
confidence: 83%
“…The quality of evidence for both was moderate due to imprecision. At 20 mg, Tuk 116 reported a +5.9% PSG SE versus placebo.…”
Section: Quality Of Sleepmentioning
confidence: 95%
See 1 more Smart Citation
“…The greatest challenge is that the agreement between EEG parameters and drug effect is not yet clear in many situations . It has been claimed that a better understanding of the clinical meaning of EEG parameters would be obtained if an alternative measure of drug effect were performed in combination with EEG recording .…”
mentioning
confidence: 99%
“…8,9 The greatest challenge is that the agreement between EEG parameters and drug effect is not yet clear in many situations. 10 It has been claimed that a better understanding of the clinical meaning of EEG parameters would be obtained if an alternative measure of drug effect were performed in combination with EEG recording. 1 Although it has been noticed more than two decades ago, the number of studies investigating correlations between changes in EEG parameters and well-established measures of specific drug effects is still limited.…”
mentioning
confidence: 99%